2018
DOI: 10.1088/1361-6579/aad424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a toolkit for standardizing clinical measures of muscle tone

Abstract: The BioTone toolkit provided comprehensive objective measures for assessing muscle tone in patients with UMNS. The toolkit could be useful for standardizing outcomes measures in clinical trials and for routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Therefore, the effect of device deformation was driven by the strongest participants in the study. In clinical studies using the LSMD [ 30 , 31 , 62 ], participants were not likely strong enough to deform the LSMD. Nevertheless, the need for a correction at all remains a design concern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the effect of device deformation was driven by the strongest participants in the study. In clinical studies using the LSMD [ 30 , 31 , 62 ], participants were not likely strong enough to deform the LSMD. Nevertheless, the need for a correction at all remains a design concern.…”
Section: Discussionmentioning
confidence: 99%
“…This study only included the upper-extremity LSMD for the elbow joint. Although it is likely that the LSMD knee device (discussed in [ 30 ]) behaves similar to the elbow device, since it is essentially a scaled-up version of the arm model, future studies will need to apply the testing protocol to evaluate reliability and validity of the LSMD for lower-extremity assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Ada et al 5 followed individuals with stroke up to one year and concluded that spasticity can cause contracture. However, the work by McGibbon et al 37 in traumatic brain injury, spinal cord injury and cerebral palsy suggests that there is not a clear association between spasticity and contracture.…”
Section: Discussionmentioning
confidence: 99%